Craniocerebral imaging in children with short stature. - Barros, L (1997)
To analyse the type and frequency of cranial CT and NMR imaging anomalies in children of short stature. Patients and Interventions: We studied 57 children of short stature with a mean age (+/-SD) of 10.1 +/- 3.8 years, 34 boys and 23 girls, all of them with auxometric criteria of GH deficiency. After studying the pituitary function and determination of karyotype in the girls, the children were classified in to five groups:-Isolated GHD (IGHD) (n = 32), multiple pituitary hormone deficiency (MPHD) (n = 6), neurosecretory dysfunction (NSD) (n = 8), Turner syndrome (n = 7) and idiopathic short stature (ISS) (n = 4). The imaging methods used were cranial CT or NMR.Of the 57 children studied the CT/NMR was abnormal in 37(64.9%) children. We found anomalies in 65.6% of IGHD patients, 62.5% of NSD patients, 100% of MPHD patients and 57.1% and 25% in the Turner s. patients and ISS patients respectively. The most frequent anomaly was hypoplastic pituitary found in 50% of IGHD patients, 37.5% of NSD patients and 33.3% of MPHD patients. None of the cases of Turner s. or ISS had hypoplastic pituitary. An empty sella was the second most frequent anomaly found in 7 patients (IGHD-3, MPHD-3, DNS-1). Of the 25 children in which NMR was performed, 8 had hypoplastic pituitary and stalk and 2 had interruption of the pituitary stalk and ectopic neurohypophysis.These results strengthen the necessity for CT/NMR imaging in children of short stature which, besides allowing identification of tumors, also permits the diagnosis of idiopathic GHD because of its frequent association with cranial imaging anomalies, mainly hypoplastic pituitary.